Supplement: Pollen Grains and Spores from the Upper Vardekløft Formation ( Jurassic), Jameson Land, East Greenland. - Muir, Marjorie D. (Meddelelser om Grønland, 1972)
A brief study of the pollen grains and spores in the two horizons of the Upper Vardekløft Formation (described in the accompanying paper) shows them to consist dominantly of long-ranging forms, not capable of providing close stratigraphic dates. 13 species were recognised.